Receptor Visionaries. (August 2018) - Wade, Nicholas J.
Sensory receptors were described and illustrated after they had been observed with the aid of microscopes. Most descriptions were made in the 19th century after the introduction of achromatic lenses in microscopes. In some senses (like vision), receptors were named according to their morphology whereas in others (like touch), they are known by the names of those who initially described them. Illustrations of the receptors from original sources are here combined with portraits of their originators.